KUALITAS TELUR BURUNG PUYUH JEPANG (Coturnix coturnix japonica) YANG DIBERIKAN JUS KULIT BUAH NAGA PADA AIR MINUM - Sujana I K. Y.; G. A. M. K. Dewi; M. Wirapartha (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2021)
This study aims to determine the egg quality of Japanese quail (Coturnix-coturnix japonica) given dragon fruit peel juice in drinking water. The design used was Completely Randomized Design (CRD) with four (4) treatments and four (4) replications, each replication consisted of 5 quails aged 6-10 weeks. The four treatments were: P0: drinking water without dragon fruit peel juice or control, P1: drinking water given dragon fruit peel juice as much as 1%, P2: drinking water given dragon fruit peel juice as much as 2%, P3: drinking water given dragon fruit skin juice as much as 3%. The variables observed were egg weight, egg shell weight, egg shell thickness, egg white weight, egg yolk weight, egg yolk color, HU (Haugh Unit), egg pH. The results obtained from the treatment of P0 drinking water without dragon fruit peel juice, P1 (1% dragon fruit peel juice on drinking water), P2 (2% dragon fruit peel juice on drinking water), P3 (3% dragon fruit peel juice on drinking water). That showed eggs quality such as: egg weight, egg shell eight, egg shell thickness, egg white weight, egg yolk weight, egg yolk color, HU (Haugh Unit) and pH were not statistically significant (P>0,05) between treatments. The conclusion of this study is giving gragon fruit peel juice 0%, 1%, 2%, and 3% through drinking water had the same value on in japanese quail (Coturnix-coturnix japonica) eggs. Keywords: egg weight, egg yolk color, HU (Haugh Unit), egg pH